Optimalisasi Gerakan Literasi Sekolah (GLS) melalui Program Inovatif - Ratna Widyaningrum; Ema Butsi Prihastari (Universitas Mathla'ul Anwar Banten, 2022)
OPTIMIZING THE SCHOOL LITERACY MOVEMENT THROUGH INNOVATIVE PROGRAMS.The government initiated the School Literacy Movement program as an effort to foster a culture of student literacy so that schools must have special programs to optimize the School Literacy Movement. The objectives of implementing this service are 1) Knowing the implementation of the School Literacy Movement at SDN Prawit 1 Surakarta, and 2) Disseminating innovative programs to optimize it. The method of implementing the service includes: (1) the approach method carried out starting from the survey, licensing, and providing motivation for teachers who will take part in the training (2) the method of implementing the program, including the preliminary stage, the stage of socialization and hearings, the implementation stage, and the monitoring and evaluation stage. evaluation. The target of the service is the 11 teachers of SDN Prawit 1 Surakarta. The expected result is the implementation of innovative programs for School Literacy Movement, namely the habit of reading 15 minutes (one child book, diary book, and reading award), library empowerment (mandatory hours of library visits, library ambassadors, library usage guidance, book info), literacy tree, making wall magazines, and posters (posting posters in strategic places and poster competitions between classes).